EU policy responses to Covid-19: effects on money growth, inflation, and spending - Ruiz-Ojeda, Alberto Luis (Institute of International Monetary Research, 2021)
This working paper contains some reflections on the potential consequences of the Eurozone’s policy response to the Covid-19. Let's summarise them in the following bullet points: • No fiscal contraction nor money supply reduction might be expected over a period of 3-4 years. Both government deficit/debt and M3 aggregate might continue to rise to even more unprecedented amounts, at least in peacetime. The ECB’s balance-sheet operations would accompany public budget expansions to prevent the Eurozone’s government´s policies from financial market punishment. • As a result, austerity policies, based on fiscal contractions (public spending reduction and tax cuts) are not in the Eurozone’s medium-long run horizon. Taxes simply take resources away from productive activities and cause distortions to market operators. Aggregate demand multipliers are formidable theoretical artefacts that take for granted the absence of pro-cyclical effects. A great deal of research has recently been done to refute the Keynesian tradition on the robust historical dataset. • Getting back to monetary stability would be much tougher for the Eurozone than it should be in rational terms. Sadly, I recognise that the EU’s constitutional counterfeits facilitate rather than refrain from monetary disequilibria. In the absence of an EU centralised (federal), lithe governmental decision-making (comitology is omnipresent), the ECB rises like the saviour for all seasons in the shape of a universal liquidity provider. • Effectively, double-digit inflation would be the inevitable consequence of the failure of a rule-based monetary strategy for the Eurozone. Along with it, weak productivity recovery and private sector zombification pave the path to Japan-like stagflation.
Keywords: COVID-19; Política monetaria; Política fiscal; Inflación; Déficit público; Deuda pública; Gasto público; monetary policy; fiscal policy; inflation; money growth; public deficit; public debt; ECB Quantitative Easing Programmes; public spending; economic recovery